In vitro evaluation of the action of irrigating solutions associated with intracanal medications on Escherichia coli and its endotoxin in root canals - Maekawa, Lilian Eiko [UNESP]; Valera, Marcia Carneiro [UNESP]; de Oliveira, Luciane Dias [UNESP]; Talge Carvalho, Claudio Antonio [UNESP]; Koga-Ito, Cristiane Yumi [UNESP]; Cardoso Jorge, Antonio Olavo [UNESP] (Universidade de São Paulo (USP), Faculdade de Odontologia de Bauru, 2011)
Objective: The purpose of this study was to evaluate the efficacy of auxiliary chemical substances and intracanal medications on Escherichia coli and its endotoxin in root canals. Material and Methods: Teeth were contaminated with a suspension of E. coli for 14 days and divided into 3 groups according to the auxiliary chemical substance used: G1) 2.5% sodium hypochlorite (NaOCl); G2) 2% chlorhexidine gel (CLX); G3) pyrogen-free solution. After, these groups were subdivided according to the intracanal medication (ICM): A) Calcium hydroxide paste (Calen (R)), B) polymyxin B, and C) Calcium hydroxide paste+2% CLX gel. For the control group (G4), pyrogen-free saline solution was used without application of intracanal medication. Samples of the root canal content were collected immediately after biomechanical preparation (BMP), at 7 days after BMP, after 14 days of intracanal medication activity, and 7 days after removal of intracanal medication. The following aspects were evaluated for all collections: a) antimicrobial activity; b) quantification of endotoxin by the limulus Amebocyte lysate test (LAL). Results were analyzed by the kruskal-wallis and Dunn's tests at 5% significance level. Results: The 2.5% NaOCl and CLX were able to eliminate E. coli from root canal lumen and reduced the amount of endotoxin compared to saline. Conclusions: It was concluded that 2.5% NaOCl and CLX were effective in eliminating E. coli. Only the studied intracanal medications were to reduce the amount of endotoxin present in the root canals, regardless of the irrigant used.
Keywords: Endotoxins; Sodium hypochlorite; Chlorhexidine; Calcium hydroxide; Polymyxin B